A low‐complexity QoS aware resource allocation algorithm for multi pair device‐to‐device (D2D) communications. Issue 10 (15th May 2017) - Bagheri, Hamidreza; Miranda Bonomi, Fernando Alberto; Katz, Marcos
Abstract: Device‐to‐device (D2D) communication underlaying cellular networks is considered a promising technology to enhance network throughput, spectral efficiency, and performance of next generation networks. However, these potential gains hinge on the exploiting mechanism for resource sharing between cellular users (CUs) and D2D pairs. In this paper, we analytically formulate the problem of resource sharing as an optimization problem to maximize network throughput while guaranteeing the required quality‐of‐service (QoS) for both cellular and D2D users. We propose a low‐complexity four‐step resource allocation algorithm to address the optimization problem. We exploit a distance‐based method to derive a resource reuse candidacy graph (RCG) and three exclusive regions (ERs) to evaluate the suitability of resource sharing between each CU and D2D pair. Then, we use a paring mechanism to find the optimal set of D2D pairs for spectrum sharing with each CU to maximize network throughput. The performance of the proposed algorithm is investigated in terms of network throughput, outage probability, and computational complexity. Numerical results show that the proposed algorithm provides high throughput and spectrum utilization with low complexity while efficiently guaranteeing QoS for CUs and D2D pairs. Abstract : This paper proposes a low‐complexity resource allocation algorithm for device‐to‐device (D2D) communications enabling spectrum sharing of each cellular user with multiple D2D pairs and providing high throughput and spectrum efficiency while guaranteeing quality‐of‐service for cellular and D2D communications.